Higher Abdominal Adiposity Is Associated With Lower Muscle Strength in Chilean Adults - Palacio, Ana Cristina; Díaz-Torrente, Ximena; Quintiliano-Scarpelli, Daiana (Frontiers in Nutrition, 2022)
Handgrip strength (HGS) is a well-established indicator of muscle strength and a reasonable clinical predictor of metabolic health and diseases. This study explores the association between relative muscular strength and abdominal obesity (AO) in healthy Chilean adults. A convenience sample was recruited (n=976) between 2018 and 2020. HGS was determined by dynamometry. Anthropometry (weight, height, waist, and mid-arm circumference) and physical activity were also measured. Relative HGS (RHGS) was calculated by dividing maximum HGS of the dominant hand by body mass index. AO was defined as a waist circumference (WC) >88 cm for women, and >102 cm for men. From the sample, 52.6% were women, 56.4% had excessive weight and 42.7% had AO. Absolute and RHGS were greater in men compared to women (p<0.001) and decreased with age in both sexes. We observed a moderate negative correlation between WC and RHGS (rho = -0.54, and rho = - 0.53, for men and women, respectively). RHGS was lower in individuals with AO, independent of age and sex (p<0.05). For each cm increase in WC, the odds of low RHGS (< 25th percentile) increased by 12% and 9% for men and women, respectively. AO related to higher odds for low RHGS (OR: 1.72; 95% CI: 1.23–2.41). In our sample of healthy adults, higher AO was associated with lower muscle strength measured by dynamometry.